(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article explores recent trends and innovations in second and foreign language (L2) listening, including the use of digital tools, multimedia resources, and adaptive learning technologies. It also discusses the growing importance of authentic materials, interaction-based listening activities, and insights from cognitive processing research that influence the design of listening curricula. These challenges necessitate a thoughtful approach to instruction that accommodates varying levels of proficiency.